Acoustic similarity and perceptual similarity between Tripolitania-Libyan arabic vowels and english vowels produced by Libyan EFL learners - Said, Kalthoum Ramadan M. (2021)
It is common that learners of English as a foreign language (EFL) struggle in acquiring English sounds, particularly in producing and perceiving English vowels. Second language speech perception models such as the Second Language Linguistic Perception Model (L2LP) (Escudero, 2005) claimed that the EFL learners encounter many difficulties in producing non-native vowels because they perceive the vowels inaccurately, indicating that the difficulties in the production of non-native vowels have a perceptual basis. Previous studies argued that the problem with L2 learning results from assimilation into L1 categories but many studies did not directly test this hypothesis. Therefore, this thesis aims to examine the influence of the acoustic similarity between Tripolitania-Libyan Arabic (TLA) vowels and English vowels on the perceptual similarity of English vowels by Libyan EFL learners. Seventy Libyan participants were recruited in this study. They performed two tasks: two speech production tasks and a speech perception task. The production task included producing TLA vowels and English vowels that were embedded in carrier sentences in the two languages, while the perception task examined the assimilation of English vowels to specific TLA sounds. The findings of the production tasks for the TLA vowels showed that the differences between the acoustic measurements of TLA vowels and English vowels produced by Libyan EFL learners are not significant. However, when the English vowels produced are compared with those produced by English native speakers as reported in Deterding (1995), with the exception for /i:/ and /ɜ:/, the vowels produced by Libyan EFL learners occupied a different vowel space. There was a bigger overlap found between the English vowels produced with TLA vowels providing empirical evidence of assimilation of L2 vowels into L1 vowel categories. The results of Euclidean Distance (ED) calculated predicted that the English /ɪ, e, æ, ɜ, ʌ, ɑ:, ɒ, ʊ, ɔ:/ are the most difficult vowels for Libyan learners to perceive as these vowels could be assimilated to more than one TLA vowels, while the /i:/ and /u:/ are easy to perceive as they are predicted to be assimilated to only their corresponding vowels in TLA. This was subsequently confirmed in the perception task where these vowels were indeed found to be assimilated to more than one TLA vowel categories. The single linear regression test also revealed that the acoustic distance between English and TLA vowels can predict 43% of the degree of perceptual similarity between English vowels and TLA vowels. These results help to improve the understanding of the influence of native accent of learners on production and perception of FL sounds. In sum, the findings of this study confirmed that the acoustic similarity between L1 and foreign language (FL) vowels can successfully predict the difficulties faced by the EFL learners during the FL acquisition process. From a theoretical perspective, the results support the predictions made by L2LP that the acoustic between L1 vowels and L2 vowels can influence the perception of L2 vowels.